Новые и редкие формы инфузорий подотряда тинтинноинеи (Tintinnoinea) из придунайских лиманов в пределах Украины - Морозовская, О.И.; Полищук, В.В. (Вестник зоологии, 1969)
В пробах зоопланктона, собранных в придунайских лиманах Ялпух, Кагул, а также на взморье в районе Делюкова кута (около выхода Очаковского устья Килийской дельты Дуная), мы обнаружили три новые формы инфузорий тинтинноиней, принадлежащих к двум родам. Физико-географическая, гидрологическая и гидрохимическая характеристика указанных водоемов, а также вопросы их генезиса приводятся в работах Ю. М. Марковского (1955), А. М. Алмазова и Ю. Г. Майстренко (1961), К. С. Владимировой и К. К. Зерова (1961); М. В. Товбина, М. Б. Фельдман и Ю. Г. Майстренко (1961), А. М. Алмазова и др. (1963), Г. А. Ена-ки (1966) и др. На нахождение тинтинноиней в зоопланктоне лиманов Ялпух и Кагул указывает М. Л. Пидгайко (1957), однако не устанавливает их видовой принадлежности.
Ниже дается описание найденных нами форм инфузорий. New forms of Infusoria are described of the Tintinnoinea suborder from the Danube estuaries Yalpukh and Kagul.
Tintinnidium species shells are narrow, oblong, cylindrical, rounded to the hinder part, often broadened in the aboral part or noticeably narrowed in the orifice. The length of the shells is 112—250 pm, the width of the orifice — 64—88 pm. The edge of the orifice is rough. The walls are jelly-like, soft, easily deformable, quantity and dimensions of agglomerated particles increase from the oral to aboral end.
In Tintinnopsis urnula f. danubiana f. n. the shells are small (their length — 59.8— 66.5 pm, the width of the orifice 35.1—41.4 pm) and slightly bandaged approximately in the upper third. The hinder end of the shell is closed and smoothly rounded. In the suboral region three-four prominent spiral rings are distinctly seen. The wall is thin, homogeneous, the body of infusoria is often seen through it. Agglomeration is not thick, consists of detrite pieces of a medium size.
At coastal waters against the Kiliiskaya delta of the Danube infusoria of the new form, species Tintinnopsis meunieri Koi. et Camp, are found, which differ from the north-western part of the Black Sea in a bigger size and less developed tail process.